2021
DOI: 10.1002/adfm.202108950
|View full text |Cite
|
Sign up to set email alerts
|

Polaron Hopping Induced Giant Room‐Temperature Magnetodielectric Effect in Disordered Rutile NiNb2O6

Abstract: A majority of the existing magnetodielectric (MD) effects based on spin-lattice coupling or magnetic transitions are either too weak or far below room temperature, which challenges the potential applications of MD materials. Here, a giant room-temperature MD coefficient of −62% at 1 Tesla (T) in disordered rutile NiNb 2 O 6 (r-NiNb 2 O 6 ) ceramic in terms of the spin-dependent polaron hopping is demonstrated. The r-NiNb 2 O 6 exhibits a near-room-temperature dielectric relaxation, which is ascribed to the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…A view point should be set forth that the application objects of ECM do not only limit to the inhomogeneous systems. Moreover, ECM is also suitable to describe dipolar-type dielectric response in light of the equivalent circuit in the inset of figure 3 [144,147,230]. This equivalent circuit is the parallel of the capacitance C ∞ element and the series of the capacitance ∆C and a distributed CPE element, and the total admittance of this circuit can be obtained as:…”
Section: Ecmsmentioning
confidence: 99%
See 1 more Smart Citation
“…A view point should be set forth that the application objects of ECM do not only limit to the inhomogeneous systems. Moreover, ECM is also suitable to describe dipolar-type dielectric response in light of the equivalent circuit in the inset of figure 3 [144,147,230]. This equivalent circuit is the parallel of the capacitance C ∞ element and the series of the capacitance ∆C and a distributed CPE element, and the total admittance of this circuit can be obtained as:…”
Section: Ecmsmentioning
confidence: 99%
“…The systematic analyses of the dielectric anomalies in broadband frequency range (from acoustic-to optical-frequency) are extremely significant and are able to provide one detailed and unique insight into abundant underlying fundamental physics. It involves phase transition , quantum paraelectric and quantum electric-dipole liquids [57][58][59][60][61][62][63][64][65][66], ferroic domain wall (DW) motion [67][68][69][70][71][72][73][74], short-range polar region, nano-microdomain and multiglass behaviors [29,, heterogeneous interface effects [51,, the origin of magnetoelectric and magnetodielectric (MD) phenomena [39-41, 48, 139, 140, 145-148], the motion of charged point defects and related defect complexes [115,143,, the transport mechanisms of localized charged carriers and polarons [24,138,144,147,164,169,, electronic phase separation [139,140], charge order-disorder [24,51,131,185], spin-lattice interaction [39,40,48], electron-phonon interaction [215], optical phonon soft modes [216], electronic critical points transitions [215,…”
Section: Introductionmentioning
confidence: 99%
“…20,49 The magnetic field may have oriented these defect clusters. In rutile NiNb 2 O 6 materials, the ion's spin alignment and the strength of the spin-lattice coupling are both influenced by the magnetic field that is being applied, 31 and modifying the dielectric response stands to reason. In (Nb 0.5 La 0.5 ) x Ti 1-x O 2 ceramics, the magnetic field may affect the defect clusters inside the ceramics, 30 thereby increasing R1 and R2's activation energy.…”
Section: F I G U R Ementioning
confidence: 99%
“…However, studies of improving giant permittivity performance via this method are rarely reported 30 . Due to the magnetic field having a regulatory effect on cluster defects 31 , magnetic slip casting is a promising approach to modify EPDD 30,32–35 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation